Bipolar ablation of epicardial posteroseptal accessory pathway. (8th August 2019) - Derejko, Pawel; Miszczak‐Knecht, Maria; Sliwka, Michal; Dzwonkowska, Dobromiła; Bieganowska, Katarzyna
Abstract: We present a case of a 16‐year‐old male with WPW syndrome, referred for ablation after being resuscitated from cardiac arrest. Bipolar transseptal RF ablation successfully destroyed rapidly conducting epicardial posteroseptal accessory pathway after three failed attempts of endo‐ and epicardial ablation.